TATA KELOLA BANTUAN LOGISTIK KORBAN BENCANA BANJIR DI KECAMATAN SETU KOTA TANGERANG SELATAN - Gerry Purwanto Syaeful Rochman (Jurnal MoZaiK, 2020)
The importance of governance in the distribution of logistical assistance during emergencies involves stakeholders. Coordination of various elements/elements in the mechanism for distributing aid requires coordination. Besides, the establishment of appropriate management and monitoring is carried out to ensure that all assistance is maintained until the aid is distributed on target. The purpose of this study is to find Governance in the distribution of BPBD Logistics in South Tangerang City according to governance based on the theory of effectiveness in management, the method used is qualitative, data collection techniques data collection can be obtained from observations, interviews, documentation, and combination / triangulation. ,research data sources of primary and secondary data. There are obstacles if Logistics Management is constrained which can hinder the distribution mechanism if the elements / elements do not understand the existing SOP mechanism. The focus of the research is 1 Logistics distribution mechanism for victims of natural disasters in South Tangerang City, by describing the stakeholders involved in the logistics distribution mechanism and the distribution of aid. 2) Identifying the implementation of the aid distribution mechanism. 3) Designing a mechanism that is more effective in distributing logistics assistance. Keywords: Governance, Logistic, Disaster management